Readmission and Prolapse Recurrence After Abdominal and Vaginal Apical Suspensions in Older Women. Issue 6 (December 2016) - Sanses, Tatiana V. D.; Hanley, Jan M.; Zhang, Peter; Richter, Holly E.; Gambert, Steven R.; Saigal, Chris S.
Abstract : OBJECTIVE: Our objective was to evaluate 30-day readmission, 12-month prolapse recurrence, and complications after apical surgeries in older women. METHODS: A retrospective cohort study was conducted using 2002–2011 Medicare data in women 65 years or older who underwent abdominal sacrocolpopexy with synthetic mesh, vaginal uterosacral, or sacrospinous colpopexy with 12 months follow-up. Vaginal mesh procedures were excluded. The primary outcome was 30-day inpatient readmission. Secondary outcomes were complications and prolapse recurrence, defined as either reoperation or pessary insertion. We used Pearson χ 2, Fisher exact tests, and analyses of variance to examine difference between surgical treatment groups. Odds ratios (ORs) utilizing Charlson Comorbidity Index, age, race, and procedure type were calculated to assess the differences in the outcomes probability. RESULTS: Of 3, 015 women, 863 underwent abdominal sacrocolpopexy, 510—uterosacral and 1, 642—sacrospinous ligament suspensions. The 30-day readmission was 7.4% (95% confidence interval [CI] 5.7–9.2%; OR 2.4, 95% CI 1.7–3.5, P <.01) after abdominal sacrocolpopexy and 4.5% (95% CI 2.7–6.3%; OR 1.3, 95% CI 0.8–2.1, P =.3) after uterosacral compared with 3.5% (95% CI 2.6–4.4% P <.01) after sacrospinous ligament suspensions. Prolapse recurrence did not differ between the groups (8.2%, 95% CI 6.4–10.1%; 10.6%, 95% CI 7.9–13.3%; and 9.9%, 95% CI 8.4–11.3%, P =.3, respectively). Women had 30-day gastrointestinal complications (6.1%, 95% CI 4.5–7.7%; 1.2%, 95% CI 0.2–2.1%; and 1.1%, 95% CI 0.6–1.6%, P <.01), surgical site infections (5.9%, 95% CI 4.3–7.5%; 3.1%, 95% CI 1.6–4.7%; and 3.7%, 95% CI 2.8–4.6%, P =.01), genitourinary complications (10.9%, 95% CI 8.8–13%; 17.7%, 95% CI 14.3–21%; and 13.6%, 95% CI 12–15.3%, P <.01), and medical complications (7.4%, 95% CI 5.7–9.2%; 7.8%, 95% CI 5.5–10.2%; and 4.4%, 95% CI 3.4–5.4%, P <.01; all after abdominal sacrocolpopexy, uterosacral, and sacrospinous ligament suspensions, respectively). CONCLUSION: Vaginal apical suspensions compared with abdominal sacrocolpopexy with synthetic mesh are associated with lower rates of postoperative 30-day readmission without an increase in prolapse recurrence among older women. Abstract : Supplemental Digital Content is Available in the Text.Vaginal apical prolapse suspensions compared with abdominal sacrocolpopexy are associated with lower rates of postoperative 30-day readmission without a 12-month prolapse recurrence increase among older women.